Kualitas Pelayanan E-Health Sebagai Alternatif Antrian Online Di Puskesmas Kota Surabaya - Leksono, Totok Minto; Arsitha, Ditha Arsya (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2024)
Public services are the government's obligations and responsibilities in providing public services for the community. Improvements in public services arise from the public continuously voicing their demands for better public services. . In the midst of the rapid development of information and communication technology (ICT), E-Government is present as an innovative solution to answer community needs and improve the quality of public services. The development of information and communication technology (ICT) has brought a breath of fresh air to the world of health. E-Health, or electronic health, exists as an innovative solution to improve the quality of health services and reach a wider community. E-Health can automate many manual processes in health services, such as patient registration, electronic medical records, and telemedicine. One of the cities that has implemented E-Health innovation is the City of Surabaya. It has been explained and supported by the central government through Government Regulation Number 46 of 2014 concerning Health Information Systems. This regulation aims to realize the implementation of a reliable, integrated and electronic-based health information system which is in line with the aim of E-Health for the City of Surabaya to improve the quality of health services through the use of information technology. The aim of this research focuses on describing the quality of e-health services as an alternative to online queuing at Surabaya City Health Centers. The method used in this research is using a library study research method with a qualitative approach. Data collection uses data collection techniques online or from the internet by looking at websites and journals on Google Scholar related to the article Quality of E-Health Services as an Alternative to Online Queues at Surabaya City Health Centers. To describe the quality of E-Health services as an alternative to online queues at Surabaya City Health Centers, we use the E-GovQual indicators which include ease of use, trust, reliability, content and appearance of information. ), and citizen support (supporters). The results of the description of the quality of E-Health services in the city of Surabaya can be implemented well in the community, although there are several obstacles but they can be overcome by the government, especially in supporting points, on the Surabaya City E-Health website there is no help desk feature but this does not mean it is completely make people trouble